2020
DOI: 10.1021/acs.analchem.0c00274
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Gold Nanowires as Stretchable and Wearable Epidermal Ion-Selective Electrode for Noninvasive Multiplexed Sweat Analysis

Abstract: The noninvasive continuous analysis of human sweat is of great significance for improved healthcare diagnostics and treatment in the future, for which a wearable potentiometry-based ion-selective electrode (ISE) has attracted increasing attention, particularly involving ion detection. Note that traditional solid-state ISE electrodes are rigid ion-to-electron transducers that are not conformal to soft human skin and cannot function under stretched states. Here, we demonstrated that vertically aligned mushroom-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 46 publications
3
89
0
Order By: Relevance
“…AuNWs were prepared using as eed-mediated method on an umber of (3-aminopropyl)trimethoxysilane (APTMS)modified polymer substrates including PDMS,E coflex, polyethylene terephthalate,a nd polymethylmethacrylate. [30][31][32][33] Note that APTMS served as ab ifunctional molecular glue with the amine end interacting with AuNWs and the silane end bonding to substrate surfaces,and the film exhibited extremely high stretchability up to 800 %s train. [30] Cyclic voltammetric characterization of AuNWs-based electrodes in both H 2 SO 4 and Fe(CN) 6 3À/4À solution revealed that the EC performance remained stable in the strain range of 0-50 %, [31] and the sensor displayed high catalytic activity to H 2 O 2 electroreduction over aw ide range of concentrations, from 40 mm to 15 mm.…”
Section: Minireviewsmentioning
confidence: 99%
“…AuNWs were prepared using as eed-mediated method on an umber of (3-aminopropyl)trimethoxysilane (APTMS)modified polymer substrates including PDMS,E coflex, polyethylene terephthalate,a nd polymethylmethacrylate. [30][31][32][33] Note that APTMS served as ab ifunctional molecular glue with the amine end interacting with AuNWs and the silane end bonding to substrate surfaces,and the film exhibited extremely high stretchability up to 800 %s train. [30] Cyclic voltammetric characterization of AuNWs-based electrodes in both H 2 SO 4 and Fe(CN) 6 3À/4À solution revealed that the EC performance remained stable in the strain range of 0-50 %, [31] and the sensor displayed high catalytic activity to H 2 O 2 electroreduction over aw ide range of concentrations, from 40 mm to 15 mm.…”
Section: Minireviewsmentioning
confidence: 99%
“…For wearable sensors, the device may often endure with strains. Cheng et al recently fabricated a stretchable sensor array with gold-based vertically aligned nanowires (V-AuNWs) as the solid contact material for multimodal sweat monitoring including Na + , K + and pH ( Figure 10D,E) [85,86]. The SC-ISEs array was prepared by using PDMS as flexible substrate.…”
Section: Sweat Ion Detectionmentioning
confidence: 99%
“…(E) The Na + , K + and pH sensing from 0% to 30% stretching. Reprinted with permission from[86], Copyright (2020) American Chemical Society.…”
mentioning
confidence: 99%
“…However, the stability of the device was limited by only three-day storage owing to the limited stability of the enzyme. In addition to glucose sensing applications, the idea of using metallic nanowires is versatile with respect to being adapted for other applications in electroanalysis, such as the detection of electrolytes [88]. More examples of the development of electrolyte biosensors will be discussed further in Section 2.3.…”
Section: Developing Glucose Sensorsmentioning
confidence: 99%
“…A nanowire is an interesting material to be applied for flexible and stretchable electrodes. An example of AuNWs is for improving the stretchability of traditional rigid solid-state ion-selective electrode (ISE) [88]. The AuNW-based ISE was fabricated by vertically aligning and bonding AuNWs to PDMS elastomers using facile solution-based method and a seed-mediated approach combining photolithography.…”
Section: Developing Electrolyte Sensorsmentioning
confidence: 99%